Microbiological spectrum of causative agents of healthcare-associated infections isolated in Ukraine in 2022-2023 (Environment & Health, 2025)
The purpose of the study is to identify strains of microorganisms, pathogens of infections associated with the provision of medical care, isolated from patients in Ukraine in 2022-2023.Research materials and methods: Strains of microorganisms that came to the Reference Laboratory for the diagnosis of tuberculosis, bacterial, parasitic and especially dangerous pathogens of the Public Health Center of the Ministry of Health of Ukraine from the regional centers of disease control and prevention and health care institutions of Ukraine were studied. Microorganisms were identified using the VITEK 2 microbiological analyzer, MIC Test strips. 1454 versus 343 strains isolated in 2022 were analyzed using the WHONET computer program.Research results: In 2023, the number of cultures of opportunistic microorganisms, the probable causative agents of infections associated with the provision of medical care, increased more than 4 times. 1471 cultures were obtained against 358 in 2022. The largest number of strains came from healthcare facilities in Kyiv (22.4%), Dnipropetrovsk (14.4%), Lviv (11.6%), Khmelnytskyi (10.7%), Zaporizhia (8.2% ), Odesa (4.8%), Rivne (3.9%), Ivano-Frankivsk (3.7%), Cherkasy (2.5%), Zakarpattia (2.5%), Kirovohrad (2.2% ) regions. The specific weight of other regions of Ukraine, where crops came from, excluding those where active hostilities are taking place (Donetsk, Luhansk, Kherson regions), ranged from 0.4% to 1.8%.Among the studied cultures, gram-negative microorganisms dominated - 92%, gram-positive - 8%.K .pneumoniae - 35.2% (30.6%); A. baumannii - 26.0% (19.0%); P. aeruginosa - 19.9% (19.2%); E. coli - 5.3% (15.2%); E. cloacae - 2.3% (7.3%); P. mirabilis - 1.5% (1.7%); S. aureus - 4.5% (1.7%); S. epidermidis - 1.2% (0.9%); S. haemolyticus - 1.1% (1.5%); E. faecalis - 0.6% (0.3%); E. faecium - 0.6% (2.0%); others - 1.8% (0.6%).According to the place of localization, culture strains were isolated: from wounds - 1045 cultures - 71.9% (45.5%), from blood - 263 cultures - 18.1% (20.7%), from cerebrospinal fluid (SMR) - 52 cultures - 3.6% (3.2%), from urine - 82 cultures - 5.6% (26.2%), from the external environment (ZS) - 12 cultures - 0.8% (4.4%).CONCLUSIONS1. Based on the results of the microbiological analysis, the etiological structure of the pathogens of infections associated with the provision of medical care in Ukraine for 2022-2023 was determined.2. In 2023, the number of cultures of opportunistic pathogens, the probable causative agents of infections associated with the provision of medical care, received by the Public Health Center of the Ministry of Health of Ukraine increased by more than 4 times, 1471 cultures were obtained against 358 in in 2022.3. The largest number of strains came from healthcare facilities in Kyiv (22.4%), Dnipropetrovsk (14.4%), Lviv (11.6%), Khmelnytskyi (10.7%), Zaporizhia (8.2%),4. The microbial landscape of the sent cultures is represented by the most widespread microorganisms that are subject to sentinel epidemiological surveillance of antimicrobial resistance in Ukraine. Among the studied cultures, gram-negative microorganisms dominated - 92%, gram-positive - 8%.
Keywords: bacteria; healthcare-associated infections; epidemiological surveillance